2011
DOI: 10.1002/hbm.21355
|View full text |Cite
|
Sign up to set email alerts
|

Human cortical theta reactivity to high‐frequency repetitive transcranial magnetic stimulation

Abstract: Electroencephalography (EEG) can directly monitor the temporal progression of cortical changes induced by repetitive Transcranial Magnetic Stimulation (rTMS) and facilitate the understanding of cortical and subcortical influences in the genesis of oscillations. In this combined rTMS/EEG study, we aimed to investigate changes in oscillatory activity after high-frequency ($11 Hz) rTMS relative to the number of applied pulses. Twenty intermittent trains of 20 or 60 rTMS pulses were delivered over the human primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 79 publications
3
7
0
Order By: Relevance
“…This supported our previous study that showed a higher cortical oscillations of θ (4–7 Hz) compared to µ (10–12 Hz) and β (13–30 Hz) up to 20 seconds after intermittent trains of 60 pulses of high frequency magnetic stimulation (∼ 11 Hz) to the primary motor cortex at rest [26]. We proposed that the increase in θ power modulation may be due to the independent theta generators that are not confined to the hippocampus but also present near the brain surface as demonstrated by animal studies [40], [41], and human intracranial EEG recordings [41][44].…”
Section: Discussionsupporting
confidence: 92%
“…This supported our previous study that showed a higher cortical oscillations of θ (4–7 Hz) compared to µ (10–12 Hz) and β (13–30 Hz) up to 20 seconds after intermittent trains of 60 pulses of high frequency magnetic stimulation (∼ 11 Hz) to the primary motor cortex at rest [26]. We proposed that the increase in θ power modulation may be due to the independent theta generators that are not confined to the hippocampus but also present near the brain surface as demonstrated by animal studies [40], [41], and human intracranial EEG recordings [41][44].…”
Section: Discussionsupporting
confidence: 92%
“…This was not the case for local alpha power at the source level where we found the alpha and beta power increase only in rhythmic rTMS. Our findings are in line with previous studies where participants received conventional stimulation intensities of rTMS (80-100% of resting motor threshold) applied over the left M1 at rest [22,23].…”
Section: Electrophysiological Effects Of Low-intensity Rtmssupporting
confidence: 93%
“…This work served as a demonstration of the effect of rTMS on regional and interregional synaptic transmission via the induction of cortical oscillations. More recent work by Azila Noh and Fugetta demonstrated broader effects of high frequency rTMS (11 Hz) on theta, mu, and beta frequency bands. Sokhadze et al (2009) further applied these techniques to demonstrate the potential therapeutic benefit of rTMS in autism to provide a means of altering neuronal plasticity through a presumed mechanism of enhanced cortical gamma oscillations.…”
Section: Noninvasive Brain Stimulationmentioning
confidence: 98%